Improving Quality of Life in Geriatric with Pain due to Scoliosis and Old Compression Fracture: A Case Report - Dewantari, Easy Orient; Putriheryanti, Arini (Faculty of Medicine, Universitas Airlangga, 2024)
Scoliosis frequently causes problems in geriatrics, particularly pain. Pain that persists for a long time can result in a decreased quality of life and disability. Thus, pain management is needed in patients with scoliosis. We report the case of a 71-year-old man referred from the Neurology Department with pain due to scoliosis and an old compression fracture, making him incapable of walking, became dependent, and had a high risk of falling, thus resulting in a decreased quality of life. Physical examination revealed hyperkyphotic thoracal, tenderness and spasms on the paralumbar muscles, with no weakness in the extremities but decreased sensory function on both dorsum of the feet. The patient also had decreased chest expansion. The patient was conservatively managed. The goals of this treatment are to relieve pain, improve sensory function, and improve the quality of life. He underwent a staged rehabilitation program, starting from a combination of Transcutaneous Electrical Nerve Stimulation (TENS) and microwave diathermy, breathing, and core muscle strengthening exercises. After 10 weeks, there was an improvement in pain, risk of falls, chest expansion, and quality of life. Improving the quality of life of geriatric patients requires a multi-dimensional approach. Relieving pain, enhancing cardiorespiratory endurance and preventing falls were the main goals of this patient. Each exercise must be safe considering the patient's age, health condition, and vertebral fractures. Family support is important to monitor and encourage patient during the program.